Plant-Based Natural Resource Management Strategies Using Fruits for Cholesterol Regulation - Damayanti, Ida Ayu Manik; Wulansari, Nadya Treesna; Megayanti, Sri Dewi (West Science Nature and Technology, 2025)
Cardiovascular diseases remain a leading cause of global mortality, with hypercholesterolemia representing a major modifiable risk factor. Growing interest has emerged in plant-based strategies, particularly fruit utilization, as sustainable approaches for cholesterol regulation. This study aimed to systematically review the pharmacological mechanisms of fruit-derived secondary metabolites involved in cholesterol lowering and to explore their relevance within plant-based natural resource management. A systematic literature review was conducted following PRISMA guidelines using ScienceDirect, PubMed, and Google Scholar databases. Evidence from in vivo and in vitro studies demonstrates that various fruits including Gedong Gincu mango, sweet orange, red dragon fruit, buni fruit, Rosa roxburghii, pineapple, Synsepalum dulcificum, mulberry, and Hiyung cayenne pepper contain bioactive secondary metabolites such as flavonoids, phenolics, anthocyanins, carotenoids, triterpenoids, alkaloids, saponins, dietary fiber, and antioxidant enzymes. These compounds exert cholesterol-lowering effects through multiple pharmacological pathways, including inhibition of cholesterol synthesis and absorption, enhancement of bile acid excretion, modulation of lipid metabolism–related gene expression, and reduction of oxidative stress and inflammation. Several fruit-based interventions showed significant reductions in total cholesterol and LDL levels, with some demonstrating efficacy comparable to conventional hypolipidemic agents. These findings highlight the potential of fruit-based natural resources as functional, sustainable, and scientifically supported strategies for cholesterol regulation and cardiovascular disease prevention.